Optimalisasi Implementasi Pembelajaran E-learning dan Strategi Pencegahan Covid-19 di SMAN 1 Darussalam Aceh Besar - Jakfar, Jakfar; Mulana, Farid; Adisalamun, Adisalamun; Hisbullah, Hisbullah; Azwar, Azwar (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2023)
: The Corona virus is included in a group of viruses that have the potential to cause various levels of disease severity, ranging from mild to severe symptoms. There are at least two known types of coronaviruses, namely MERS and SARS, which can cause disease. The Corona virus has the potential to cause disorders of the respiratory system, acute pneumonia, and even death. E-learning is a learning method that uses electronic technology. The utilization of a computer network is one of the platforms. as a result of the growth of computer networks, this method can be developed in a web-based form, thus allowing wider access via the internet. Google has developed a blended learning platform for schools with the intention of simplifying the paperless process of creating, distributing, and assigning assignments. This method helps teachers and students conduct learning in virtual classes, especially during the COVID period. This application allows teachers and students from various schools to communicate in an easier way. In addition, Google Classroom is also provided free of charge for educational centers and non-profit organizations. The purpose of this service is to provide counseling and workshops regarding the latest developments and scientific understanding, as well as precautions and control of COVID-19. In addition, it also aims to carry out learning training through the use of electronic media (e-learning) at SMA Negeri 1 Darussalam, Aceh-Besar.